Silicon-based negative electrode material coated with triblock copolymer coating and preparation method of silicon-based negative electrode material

By covering the triblock copolymer coating on the silicon-based negative electrode material, the problems of volume expansion and interface instability are solved, and the combination of high mechanical strength and electrical conductivity is achieved, and the performance and cycle stability of lithium-ion batteries are improved.

CN119905545APending Publication Date: 2025-04-29SHENZHEN XIANGFENGHUA TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411837916.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The application of silicon-based anode materials in lithium-ion batteries is limited by volume expansion effects and unstable electrode-electrolyte interfaces, and existing carbon-based materials and oxide coatings are prone to break during circulation, hindering the diffusion of lithium ions and resulting in a decrease in specific capacity and magnification capabilities.

Method used

A silicon-based negative electrode material coated with a triblock copolymer coating is prepared by a specific synthetic method. The triblock copolymer provides mechanical strength and ion conductivity to avoid hindering the diffusion of lithium ions.

Benefits of technology

It effectively suppresses the volume expansion effect of silicon, improves the structural stability and high ionic conductivity of silicon negative electrode materials, ensures a high-performance lithium-ion battery, and has a capacity retention rate of 89.6% after 300 weeks of cycle, with excellent cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187217120000101
    Figure BDA0005187217120000101
  • Figure BDA0005187217120000111
    Figure BDA0005187217120000111
Patent Text Reader

Abstract

The invention discloses a preparation method of a silicon-based negative electrode material coated with a triblock copolymer coating, which comprises the following steps: generating a triblock copolymer through crosslinking and polymerization, coating the triblock copolymer on the silicon-based negative electrode material, and carrying out low-temperature carbonization. Different blocks in the triblock copolymer serve as a firm mechanical skeleton and a continuous ion-conducting framework at the same time, the block A is formed by polymerizing monomers with crosslinking functional groups and can form a chemical crosslinking network structure and buffer the volume expansion effect of the silicon negative electrode, and the block B is an ion-conducting block, is formed by polymerizing ion-conducting monomers and has the ion conduction characteristic. And the triblock copolymer can simultaneously construct a mechanical support frame and form a continuous lithium ion transmission channel, and after low-temperature carbonization treatment, an interface between silicon and the triblock copolymer is reconstructed to form a strong chemical bond, so that the overall integrity is improved, a protection site is provided to prevent agglomeration, and the problem of an unstable electrode-electrolyte interface is solved. The stability of an electrochemical interface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative electrode materials, and in particular to a silicon-based negative electrode material coated with a triblock copolymer coating and a preparation method thereof. Background Art

[0002] As for negative electrode materials for lithium-ion batteries, the most widely used graphite negative electrode has a theoretical specific capacity of only 372mAh / g. However, with the development of lithium battery technology, the theoretical specific capacity of graphite negative electrode materials of 372mAh / g has begun to fail to match the development speed of existing lithium batteries, so it is urgent to develop a negative electrode material with a higher specific capacity. Silicon has an extremely high theoretical specific capacity of 4200mAh / g and is the most promising negative electrode material for the next generation of lithium-ion batteries.

[0003] However, severe volume expansion effects and unstable electrode-electrolyte interfaces are severe challenges facing the development of silicon materials. In order to solve bottleneck problems such as large size changes, low conductivity, and particle crushing of silicon electrodes during charging and discharging, a coating is usually introduced to reconstruct the surface of silicon and stabilize the silicon electrode. Both carbon-based materials and oxide coatings have been widely used in the field of silicon negative electrodes. However, due to the poor mechanical properties of carbon materials and oxides, they are easy to break during the cycle and cannot ensure long-term cycle stability. For this reason, merchants began to thicken the carbon coating on the surface of silicon composite materials. Although this can provide enhanced mechanical stability and electrolyte compatibility, it will hinder the diffusion of lithium ions, resulting in a decrease in specific capacity and rate capability. Therefore, it is necessary to propose a new solution to improve the above problems. Summary of the invention

[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a silicon-based negative electrode material coated with a triblock copolymer coating and a preparation method thereof, wherein the surface coating has better mechanical strength, will not hinder the diffusion of lithium ions, and effectively prevents the decrease in specific capacity and rate capability.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating comprises the following steps:

[0007] (1) dissolving 0.1-3.2 parts by weight of a reversible addition-fragmentation chain transfer agent in 10-40 parts by weight of anhydrous ethanol or anhydrous acetonitrile, adding 10-40 parts by weight of a crosslinking monomer, stirring and mixing, passing nitrogen to deoxygenate for 20-30 minutes, and then adding 0.02-0.5 parts by weight of an initiator, reacting for 4-8 hours to obtain an initial solution;

[0008] (2) adding 10-80 parts by weight of an ion-conducting monomer, 20-100 parts by weight of anhydrous ethanol or anhydrous acetonitrile and 0.02-0.5 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 8-20 hours to obtain a diblock compound solution;

[0009] (3) adding 10-40 parts by weight of a crosslinking monomer, 10-40 parts by weight of anhydrous ethanol or anhydrous acetonitrile, and 0.02-0.5 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 8-20 hours to obtain a triblock copolymer solution;

[0010] (4) adding 20-100 parts by weight of anhydrous ethanol or anhydrous acetonitrile and 50-150 parts by weight of a silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continuing stirring after sufficient ultrasonic dispersion, and irradiating under an ultraviolet lamp for 5-30 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400 nm, to obtain a semi-finished product solution;

[0011] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 5-10 hours at a temperature of 500-600° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0012] As a preferred embodiment, the cross-linking monomers in step (1) and step (3) are both CEA.

[0013] As a preferred embodiment, the ion-conducting monomer in step (2) is PEGMA.

[0014] As a preferred embodiment, the reversible addition-fragmentation chain transfer reagent in step (1) is one of 3-benzylsulfonylcarbonylthiosulfonylpropionic acid, cyanomethyldodecyl trithiocarbonate, and 2-cyano-2-propylbenzodisulfide.

[0015] As a preferred embodiment, the initiators in step (1), step (2) and step (3) are at least one of azobisisocyanovaleric acid, azobisisobutyronitrile, azobisisoheptanenitrile or tert-butyl hydroperoxide.

[0016] As a preferred embodiment, the silicon-based negative electrode material in step (4) is one of silicon nanoparticles, silicon oxides and silicon nanotubes.

[0017] A silicon-based negative electrode material coated with a triblock copolymer coating is prepared by the above-mentioned method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating.

[0018] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0019] The different blocks in the triblock copolymer serve as a strong mechanical skeleton and a continuous ion-conducting framework at the same time. The triblock copolymer is an ABA-type block copolymer. Block A is a cross-linked block, which is polymerized from monomers with cross-linking functional groups, and can form a chemically cross-linked network structure to buffer the volume expansion effect of the silicon negative electrode. Block B is an ion-conducting block, which is polymerized from ion-conducting monomers and has ion-conducting properties. The triblock copolymer can simultaneously construct a mechanical support framework and form a continuous lithium ion transmission channel. The triblock copolymer is compounded with silicon-based materials, which can effectively inhibit the volume expansion effect of silicon, improve the stability of the silicon negative electrode material structure, and ensure high ion conductivity, greatly improve the performance of the silicon-based negative electrode, and after low-temperature carbonization treatment, the interface between silicon and the triblock copolymer is reconstructed to form strong chemical bonds, such as Si-C and Si-OC, which increases the overall integrity, provides protection sites to prevent agglomeration, solves the unstable electrode-electrolyte interface problem, and improves the stability of the electrochemical interface.

[0020] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments: DETAILED DESCRIPTION

[0021] The present invention discloses a method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating, comprising the following steps:

[0022] (1) dissolving 0.1-3.2 parts by weight of a reversible addition-fragmentation chain transfer agent in 10-40 parts by weight of anhydrous ethanol or anhydrous acetonitrile, adding 10-40 parts by weight of a cross-linking monomer, stirring and mixing, deoxygenating with nitrogen for 20-30 minutes, adding 0.02-0.5 parts by weight of an initiator, and reacting for 4-8 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is one of 3-benzylsulfonylcarbonylthiosulfonylpropionic acid, cyanomethyldodecyl trithiocarbonate, and 2-cyano-2-propylbenzodisulfide, the cross-linking monomer is CEA, and the initiator is at least one of azobisisocyanovaleric acid, azobisisobutyronitrile, azobisisoheptanenitrile, or tert-butyl hydroperoxide.

[0023] (2) adding 10-80 parts by weight of an ion-conducting monomer, 20-100 parts by weight of anhydrous ethanol or anhydrous acetonitrile and 0.02-0.5 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 8-20 hours to obtain a diblock compound solution, wherein the diblock compound is of the PCEA-b-PEGMA type; the ion-conducting monomer is PEGMA, and the initiator is at least one of azobisisocyanovaleric acid, azobisisobutyronitrile, azobisisoheptylonitrile or tert-butyl hydroperoxide.

[0024] (3) adding 10-40 parts by weight of a cross-linking monomer, 10-40 parts by weight of anhydrous ethanol or anhydrous acetonitrile, and 0.02-0.5 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 8-20 hours to obtain a triblock copolymer solution, wherein the triblock copolymer is of the PCEA-b-PEGMA-b-PCEA type; the cross-linking monomer is CEA, and the initiator is at least one of azobisisocyanovaleric acid, azobisisobutyronitrile, azobisisoheptylonitrile, or tert-butyl hydroperoxide.

[0025] (4) adding 20-100 parts by weight of anhydrous ethanol or anhydrous acetonitrile and 50-150 parts by weight of a silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continuing stirring after sufficient ultrasonic dispersion, and irradiating under an ultraviolet lamp for 5-30 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400nm, to obtain a semi-finished solution; the silicon-based negative electrode material is one of silicon nanoparticles, silicon oxide, and silicon nanotubes.

[0026] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 5-10 hours at a temperature of 500-600° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0027] The present invention also discloses a silicon-based negative electrode material coated with a triblock copolymer coating, which is prepared by the aforementioned method for preparing the silicon-based negative electrode material coated with a triblock copolymer coating.

[0028] The following is a detailed description with reference to a number of embodiments.

[0029] Example 1

[0030] (1) 0.1 parts by weight of a reversible addition-fragmentation chain transfer agent is dissolved in 10 parts by weight of anhydrous ethanol, and then 20 parts by weight of a cross-linking monomer is added, stirred and mixed, and nitrogen is passed through to deoxygenate for 20 minutes, and then 0.02 parts by weight of an initiator is added, and the reaction is carried out for 6 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is 3-benzylsulfonylcarbonylthiosulfonylpropionic acid, the cross-linking monomer is CEA, and the initiator is azobisisocyanovaleric acid.

[0031] (2) adding 60 parts by weight of an ion-conducting monomer, 50 parts by weight of anhydrous ethanol and 0.5 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 10 hours to obtain a diblock compound solution; the ion-conducting monomer is PEGMA, and the initiator is azobisisocyanovaleric acid.

[0032] (3) adding 20 parts by weight of a cross-linking monomer, 10 parts by weight of anhydrous ethanol and 0.1 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 8 hours to obtain a triblock copolymer solution; the cross-linking monomer is CEA, and the initiator is azobisisocyanovaleric acid.

[0033] (4) adding 80 parts by weight of anhydrous ethanol and 120 parts by weight of silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continuously stirring after sufficient ultrasonic dispersion, and irradiating under an ultraviolet lamp for 8 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400nm, to obtain a semi-finished solution; the silicon-based negative electrode material is silicon nanoparticles.

[0034] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization at a temperature of 500° C. for 5 hours to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0035] Example 2

[0036] (1) 3.2 parts by weight of a reversible addition-fragmentation chain transfer agent is dissolved in 40 parts by weight of anhydrous acetonitrile, and then 40 parts by weight of a cross-linking monomer is added, stirred and mixed, and nitrogen is passed through to deoxygenate for 30 minutes, and then 0.3 parts by weight of an initiator is added, and the reaction is carried out for 4 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is cyanomethyl dodecyl trithiocarbonate, the cross-linking monomer is CEA, and the initiator is azobisisobutyronitrile.

[0037] (2) adding 10 parts by weight of an ion-conducting monomer, 80 parts by weight of anhydrous acetonitrile and 0.02 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 8 hours to obtain a diblock compound solution; the ion-conducting monomer is PEGMA, and the initiator is azobisisobutyronitrile.

[0038] (3) adding 10 parts by weight of a cross-linking monomer, 30 parts by weight of anhydrous acetonitrile and 0.5 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 16 hours to obtain a triblock copolymer solution; the cross-linking monomer is CEA, and the initiator is diisobutyronitrile.

[0039] (4) adding 20 parts by weight of anhydrous acetonitrile and 100 parts by weight of a silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continuing stirring after sufficient ultrasonic dispersion, and irradiating the solution under an ultraviolet lamp for 30 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400 nm, to obtain a semi-finished solution; the silicon-based negative electrode material is silicon oxide.

[0040] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 8 hours at a temperature of 550° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0041] Example 3

[0042] (1) Dissolving 1 part by weight of a reversible addition-fragmentation chain transfer agent in 30 parts by weight of anhydrous ethanol, adding 10 parts by weight of a cross-linking monomer, stirring and mixing, deoxygenating with nitrogen for 25 minutes, adding 0.2 parts by weight of an initiator, and reacting for 8 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is 2-cyano-2-propylbenzodisulfide, the cross-linking monomer is CEA, and the initiator is a mixture of azobisisoheptanitrile and tert-butyl hydroperoxide, with a weight ratio of 2:1.

[0043] (2) adding 80 parts by weight of an ion-conducting monomer, 100 parts by weight of anhydrous ethanol and 0.3 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 20 hours to obtain a diblock compound solution; the ion-conducting monomer is PEGMA, and the initiator is a mixture of azobisisoheptanenitrile and tert-butyl hydroperoxide, in a weight ratio of 1:1.

[0044] (3) adding 30 parts by weight of a cross-linking monomer, 40 parts by weight of anhydrous ethanol and 0.02 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 15 hours to obtain a triblock copolymer solution; the cross-linking monomer is CEA, and the initiator is a mixture of azobisisoheptanenitrile and tert-butyl hydroperoxide, in a weight ratio of 1:3.

[0045] (4) Add 100 parts by weight of anhydrous ethanol and 50 parts by weight of a silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continue stirring after sufficient ultrasonic dispersion, and irradiate under an ultraviolet lamp for 15 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400nm, to obtain a semi-finished solution; the silicon-based negative electrode material is silicon nanotubes.

[0046] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization at a temperature of 600° C. for 8 hours to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0047] Example 4

[0048] (1) dissolving 2 parts by weight of a reversible addition-fragmentation chain transfer agent in 30 parts by weight of anhydrous ethanol, adding 30 parts by weight of a cross-linking monomer, stirring and mixing, deoxygenating with nitrogen for 25 minutes, adding 0.5 parts by weight of an initiator, and reacting for 5 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is 2-cyano-2-propylbenzodisulfide, the cross-linking monomer is CEA, and the initiator is azobisisoheptanenitrile.

[0049] (2) Add 60 parts by weight of an ion-conducting monomer, 100 parts by weight of anhydrous ethanol and 0.4 parts by weight of an initiator to the initial solution obtained in step (1), and continue the reaction for 12 hours to obtain a diblock compound solution; the ion-conducting monomer is PEGMA, and the initiator is azobisisoheptanenitrile.

[0050] (3) adding 40 parts by weight of a cross-linking monomer, 40 parts by weight of anhydrous ethanol and 0.05 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 16 hours to obtain a triblock copolymer solution; the cross-linking monomer is CEA, and the initiator is azobisisoheptonitrile.

[0051] (4) Add 50 parts by weight of anhydrous ethanol and 80 parts by weight of silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continue stirring after sufficient ultrasonic dispersion, and irradiate under ultraviolet light for 18 minutes, the ultraviolet wavelength of which is 250-400 nm, to obtain a semi-finished solution; the silicon-based negative electrode material is silicon nanotubes.

[0052] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 8 hours at a temperature of 580° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0053] Example 5

[0054] (1) dissolving 2 parts by weight of a reversible addition-fragmentation chain transfer agent in 30 parts by weight of anhydrous ethanol, adding 30 parts by weight of a cross-linking monomer, stirring and mixing, deoxygenating with nitrogen for 25 minutes, adding 0.5 parts by weight of an initiator, and reacting for 5 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is 2-cyano-2-propylbenzodisulfide, the cross-linking monomer is CEA, and the initiator is tert-butyl hydroperoxide.

[0055] (2) adding 60 parts by weight of an ion-conducting monomer, 20 parts by weight of anhydrous ethanol and 0.4 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 13 hours to obtain a diblock compound solution; the ion-conducting monomer is PEGMA, and the initiator is tert-butyl hydroperoxide.

[0056] (3) adding 40 parts by weight of a cross-linking monomer, 40 parts by weight of anhydrous ethanol and 0.05 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 20 hours to obtain a triblock copolymer solution; the cross-linking monomer is CEA, and the initiator is tert-butyl hydroperoxide.

[0057] (4) Add 55 parts by weight of anhydrous ethanol and 60 parts by weight of silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continue stirring after sufficient ultrasonic dispersion, and irradiate under an ultraviolet lamp for 5 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400nm, to obtain a semi-finished solution; the silicon-based negative electrode material is silicon nanoparticles.

[0058] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 8 hours at a temperature of 580° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0059] Example 6

[0060] (1) 2.2 parts by weight of a reversible addition-fragmentation chain transfer agent is dissolved in 36 parts by weight of anhydrous acetonitrile, 40 parts by weight of a cross-linking monomer is added, stirred and mixed, nitrogen is passed through to deoxygenate for 30 minutes, 0.3 parts by weight of an initiator is added, and the reaction is carried out for 5 hours to obtain an initial solution; the reversible addition-fragmentation chain transfer agent is cyanomethyl dodecyl trithiocarbonate, the cross-linking monomer is CEA, and the initiator is azobisisobutyronitrile.

[0061] (2) adding 10 parts by weight of an ion-conducting monomer, 65 parts by weight of anhydrous acetonitrile and 0.2 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 8 hours to obtain a diblock compound solution; the ion-conducting monomer is PEGMA, and the initiator is azobisisobutyronitrile.

[0062] (3) adding 2510 parts by weight of a cross-linking monomer, 35 parts by weight of anhydrous acetonitrile and 0.4 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 16 hours to obtain a triblock copolymer solution; the cross-linking monomer is CEA, and the initiator is diisobutyronitrile.

[0063] (4) Add 60 parts by weight of anhydrous acetonitrile and 150 parts by weight of silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continue stirring after sufficient ultrasonic dispersion, and irradiate under an ultraviolet lamp for 30 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400nm, to obtain a semi-finished solution; the silicon-based negative electrode material is silicon oxide.

[0064] (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 10 hours at a temperature of 550° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

[0065] Comparative Example 1

[0066] Metallic iron is used as a grinding medium to grind silicon nanoparticles, and an organic carbon source is added to continue grinding. The ground mixture is carbonized at high temperature to obtain a carbon-coated silicon negative electrode.

[0067] Comparative Example 2

[0068] Metallic iron is used as a grinding medium to grind silicon oxide powder, and then an organic carbon source is added to continue grinding. The ground mixture is carbonized at high temperature to obtain a carbon-coated silicon negative electrode.

[0069] Comparative Example 3

[0070] Metallic iron is used as a grinding medium to grind silicon nanotube powder, and an organic carbon source is added to continue grinding. The ground mixture is carbonized at high temperature to obtain a carbon-coated silicon negative electrode.

[0071] Performance tests were performed on the above multiple embodiments and comparative examples, and the test results are shown in Table 1.

[0072]

[0073]

[0074] Table 1

[0075] Analyzing the above data, the gram capacity of the embodiments of the present invention is slightly higher than that of the comparative example, and there is no obvious advantage. This is because the carbon coating on the surface of the comparative example and the copolymer coating of the embodiments can prevent the silicon electrode from expanding. However, the mechanical properties of the carbon coating are poor and it will hinder the diffusion of lithium ions. Therefore, after 300 cycles, the cycle performance of the comparative example is greatly reduced, and the capacity retention rate is only 80% at most. The copolymer coating of the embodiment has excellent mechanical strength and good conductivity, which is beneficial to the diffusion of lithium ions. After 300 cycles, the capacity retention rate can reach 89.6%, which has excellent cycle performance and is more conducive to promotion and application.

[0076] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating, characterized in that: The following steps are included: (1) dissolving 0.1-3.2 parts by weight of a reversible addition-fragmentation chain transfer agent in 10-40 parts by weight of anhydrous ethanol or anhydrous acetonitrile, adding 10-40 parts by weight of a crosslinking monomer, stirring and mixing, passing nitrogen to deoxygenate for 20-30 minutes, and then adding 0.02-0.5 parts by weight of an initiator, reacting for 4-8 hours to obtain an initial solution; (2) adding 10-80 parts by weight of an ion-conducting monomer, 20-100 parts by weight of anhydrous ethanol or anhydrous acetonitrile and 0.02-0.5 parts by weight of an initiator to the initial solution obtained in step (1), and continuing the reaction for 8-20 hours to obtain a diblock compound solution; (3) adding 10-40 parts by weight of a crosslinking monomer, 10-40 parts by weight of anhydrous ethanol or anhydrous acetonitrile, and 0.02-0.5 parts by weight of an initiator to the diblock compound solution obtained in step (2), and continuing the reaction for 8-20 hours to obtain a triblock copolymer solution; (4) adding 20-100 parts by weight of anhydrous ethanol or anhydrous acetonitrile and 50-150 parts by weight of a silicon-based negative electrode material to the triblock copolymer solution obtained in step (2), continuing stirring after sufficient ultrasonic dispersion, and irradiating under an ultraviolet lamp for 5-30 minutes, wherein the ultraviolet wavelength of the ultraviolet lamp is 250-400 nm, to obtain a semi-finished product solution; (5) The semi-finished solution obtained in step (4) is subjected to low-temperature carbonization for 5-10 hours at a temperature of 500-600° C. to obtain a silicon-based negative electrode material coated with a triblock copolymer coating.

2. The method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating according to claim 1, characterized in that: The cross-linking monomers in step (1) and step (3) are both CEA.

3. The method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating according to claim 1, characterized in that: The ion-conducting monomer in step (2) is PEGMA.

4. The method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating according to claim 1, characterized in that: The reversible addition-fragmentation chain transfer reagent in step (1) is one of 3-benzylsulfonylcarbonylthiosulfonylpropionic acid, cyanomethyldodecyl trithiocarbonate, and 2-cyano-2-propylbenzodisulfide.

5. The method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating according to claim 1, characterized in that: The initiators in step (1), step (2) and step (3) are at least one of azobisisocyanovaleric acid, azobisisobutyronitrile, azobisisoheptanenitrile or tert-butyl hydroperoxide.

6. The method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating according to claim 1, characterized in that: The silicon-based negative electrode material in step (4) is one of silicon nanoparticles, silicon oxides, and silicon nanotubes.

7. A silicon-based negative electrode material coated with a triblock copolymer coating, characterized in that: The present invention is prepared by the method for preparing a silicon-based negative electrode material coated with a triblock copolymer coating as described in any one of claims 1 to 6.